Mobile Phone Camera-Based Indoor Visible Light Communications With Rotation Compensation - Willy Anugrah Cahyadi; Yong Hyeon Kim; Yeon Ho Chung; Chang-Jun Ahn (IEEE Photonics Journal)
Downlink visible light communication (VLC) using a mobile phone camera is presented. The proposed scheme consists of an 8 $×$ 8 light-emitting diode (LED) array for data transmission and eight white LEDs for an adequate level of illumination. The white LEDs are also used to acquire camera focus and light metering. Moreover, an efficient rotation compensation feature is provided in the form of a special header frame called keyframe to allow multiple users to receive the data simultaneously at 90°, 180°, and 270° orientations. Unlike conventional LED allocation methods for the rotation compensation, this keyframe-based method improves the data rate significantly. The experimental results demonstrate that the data rate achieves up to 1280 bps, whereas the theoretical simulations exhibit a potential data rate of up to 5120 bps using the identical LED array. The proposed scheme can be considered to be an efficient short-range camera-based VLC in an indoor environment with advanced features such as illumination, relatively high data rate, and robust camera rotation compensation for multiuser access.